2014
DOI: 10.1186/1756-3305-7-120
|View full text |Cite
|
Sign up to set email alerts
|

Papular dermatitis due to Leishmania infantum infection in seventeen dogs: diagnostic features, extent of the infection and treatment outcome

Abstract: BackgroundThis study describes immunological responses, diagnostic features, follow up and treatment outcomes from seventeen dogs with papular dermatitis due to Leishmania infection diagnosed by cytology or real time-PCR.MethodsSpecific Leishmania humoral and cellular immune responses were evaluated by means of an immunofluorescence antibody test in all cases and a delayed-type hypersensitivity (DTH) reaction to leishmanin in eight cases. The extent of infection was studied in several tissues including blood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 54 publications
8
37
0
Order By: Relevance
“…Moreover, it has been demonstrated that dissemination to the skin varies between dogs, being greater in sick and infectious dogs [20]. Therefore, lack of these changes in the majority of dogs with normal-looking skin with stage I-mild disease would further suggest a protective immune response in these dogs able to control parasite dissemination at the site of parasite inoculation and multiplication as previously proposed [11, 18]. …”
Section: Discussionmentioning
confidence: 75%
“…Moreover, it has been demonstrated that dissemination to the skin varies between dogs, being greater in sick and infectious dogs [20]. Therefore, lack of these changes in the majority of dogs with normal-looking skin with stage I-mild disease would further suggest a protective immune response in these dogs able to control parasite dissemination at the site of parasite inoculation and multiplication as previously proposed [11, 18]. …”
Section: Discussionmentioning
confidence: 75%
“…Accordingly, it is not surprising that the sensitive PCR 61 technology has gained increasing importance as an alternative method to substantiate the histological 62 diagnosis of cutaneous leishmaniasis. However, PCR performed on histological slides is often 63 complicated by the fact that DNA extracted from formalin-fixed and paraffin-embedded tissue may be 64 partially degraded and/or contains components that inhibit PCR[10]. In this context, the quality of the DNA extracted from such fixed material and the robustness of a particular amplification procedure 66 determine the diagnostic operating characteristics of a PCR for histological samples.…”
mentioning
confidence: 99%
“…Clinical signs have been observed as early as six months of age (Tarantino et al, 2001;Lombardo et al, 2014), but often it takes more than a year for a susceptible dog to develop the first clinical signs or clinicopathological abnormalities following natural exposure to sandflies bites in an endemic setting .…”
Section: Clinical Illnessmentioning
confidence: 99%